Analisis Proses Berpikir Kritis Siswa SMK Tipe Koleris dalam Memecahkan Masalah Matematika: The Analysis of Critical Thinking of Vocational High School Choleric Type Students to Solve Mathematic Problems - Ratumas Feby Purniance; Kamid Kamid; Jefri Marzal (Universitas Jambi, 2018)
Students have their own personality types which will ultimately affect their learning skills. This study aims to describe the critical thinking process of cholerist type students in solving mathematical problems. This type of research is a qualitative-descriptive study. The subjects of the study were students of SMK 5 Muaro Jambi who had participated in the district mathematics olympiad. The instruments used were personality test sheets, problem solving sheets and interview guidelines. The researcher directly observed the process of solving mathematical problems performed by the research subject. The researcher analyzed the results of the students' work in formulating questions, solving problems, and interviewing research subjects. The interview data was analyzed by means of data reduction, data exposure/categorization and subsequent conclusions. The results of this study indicate that during the problem solving process research subjects can solve problems casually, confidently and correctly. From the results of solving problems I and II it can be seen that the research subjects make decisions very quickly, directly and solve them with different steps according to the situation and the results of their thoughts on the problems faced. It can be concluded that the research subjects were able to solve the problem critically.